The process of R&D in the pharmaceutical industryTakeda Pharmaceutical Co.Ltd as a model of open innovation - Ghoul, Ferhat; Ben mamer, Wassila (Milev Journal of Research and Studies, 2018)
Research and development is the pivotal function of the pharmaceutical industry. It is a knowledge-based industry that is constantly innovating and adapting to environmental variables in order to provide appropriate treatment solutions. Japan's Takeda Pharmaceutical Company is one of the world's leading pharmaceutical laboratories. It has a wide range of research platforms in many countries. It is based on the open innovation model as a source of pharmaceutical innovation .